Rain attenuation statistics over 5G millimetre wave links in Malaysia - Mustafa Ghanim; Manhal Alhilali; Jafri Din; Hong Yin Lam (Institute of Advanced Engineering and Science, 2019)
Millimetre wave band is a solid contender to be utilized for the future 5G wireless systems deployment. Rain-induced attenuation is a major disadvantage at these frequencies. This paper presents statistics of rain-induced attenuation and rainfall data for two years of horizontally polarized links propagating at 38 GHz and 26 GHz over a terrestrial path link of 301 meters. From the analysed datasets, a rain rate around 116 mm/h exceeded at 0.01% of the time of an average year, while the links recorded 16 and 9.5 dB at the same percentage of time for 38 and 26 GHz respectively. The study aims to identify the prediction model that deliver most reasonable predictions for 5G links operating in Malaysian tropical climate. ITU-R P.530-17, Mello’s, and Ghiani’s models were all examined. Using ITU-R model, relative error margins of around 3.8%, 30% and 49.7% alongside 22.3, 9.5, 33% were obtained in 0.1%, 0.01% and 0.001% of the time for 26 and 38 GHz respectively. Curiously, ITU-R model demonstrates better predictions to measured rain attenuation with lower error probability. This study highlights the need for new prediction models for short path-length 5G links and helps to improve the design of terrestrial links operating at millimetre wave frequencies in tropical regions.